KINETIC STUDY LEACHING OF LIMONITIC NICKEL ORE WITH SULFURIC ACID SOLUTION UNDER ATMOSFERIC PRESSURE - YETTI , SAFNIL
The possibility to extract nickel from low grade laterite nickel ore has been considered recently in Indonesia. One of the appropriate process for this typical ore is hydrometallurgy under atmospheric pressure. In line with this research activity, a series of leaching experiments has been done to study kinetic behavior leaching of limonitic nickel ore in sulfuric acid solution at constant temperature and atmospheric pressure. The concentration of sulfuric acid in solution during the test is relative constant. There are three major tests that have been done which are consisted of leaching tests with temperature variation (70 degrees C, 80 degrees C, 90 degrees C and 100 degrees C), leaching tests with ore size variation (-14 + 28 mesh and -200 +325 mesh) and a leaching test with addition 20 gpl sodium chlorides. The concentration of dissolved ions was then analyzed using AAS (Atomic Absorption Spectrophotometer) in order to identify the quantity of dissolved nickel, iron and magnesium in pregnant solution. From the analysis results, relationships between percent extraction and time are obtained. From these relationships, the dissolution rate constant of ore has been determined which then used for calculating the activation energy of leaching process. Both are used to determine the step that controls the leaching process. The kinetic of leaching has referred to shrinking core model, hence the dissolution process might be controlled by the rate of diffusion through fluid film, the rate diffusion through ash layer or the rate of reaction at the interface. From the experiment results it is revealed that the higher percentage of nickel extraction (91.41%) was obtained from leaching limonitic nickel in 1M sulfuric acid solution for 24 hours of leaching. It is believed that the leaching process is controlled by the reaction rate at the interface at initial state process (? 15 minute) and by the diffusion rate of sulfuric acid through ash layer during 30 to 120 minute of leaching. The calculation results of activation energy of each rate control are 9.59 kcal /mol and 4.838 kcal/mol. Leaching of finer limonitic nickel ore (-200 +325 mesh) results in higher percentage of nickel extraction (84.35%) than that of coarser ore (-14 +28 mesh). The addition of 20 gpl sodium chloride has increased the extraction of nickel from 33.96% to 83.22% and decreased the dissolution of iron from 59.09% to 35.37%.